2017
DOI: 10.1002/cncr.31078
|View full text |Cite
|
Sign up to set email alerts
|

Biobehavioral modulation of the exosome transcriptome in ovarian carcinoma

Abstract: These findings suggest the possibility of leveraging exosomes as a noninvasive assessment of biobehavioral factors to help to direct personalized treatment approaches. Cancer 2018;124:580-6. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…We previously demonstrated that social isolation is related to the increased expression of EMT-related gene transcripts in peripheral blood exosomes. 27 The findings of the current study have extended this work by furthering our understanding of the pathways by which social risk factors may affect disease progression and by demonstrating that similar relationships are observable within tumor tissue. These results also represent what to the best of our knowledge is the first time that we have been able to map patient-level risk factors on the EMT status of the ovarian tumor itself.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…We previously demonstrated that social isolation is related to the increased expression of EMT-related gene transcripts in peripheral blood exosomes. 27 The findings of the current study have extended this work by furthering our understanding of the pathways by which social risk factors may affect disease progression and by demonstrating that similar relationships are observable within tumor tissue. These results also represent what to the best of our knowledge is the first time that we have been able to map patient-level risk factors on the EMT status of the ovarian tumor itself.…”
Section: Discussionsupporting
confidence: 55%
“…We previously have reported that patients with ovarian cancer who are experiencing higher levels of social isolation demonstrated increased expression of EMT-related gene transcripts in exosomes derived from peripheral blood. 27 Although this finding is suggestive, to our knowledge it is not known to what extent this association reflects the biology of the tumor or what molecular signaling pathways might mediate the effects of host social support levels on tumor cell biology. To address this issue, we used genome-wide transcriptional profiling to quantify associations between social isolation and EMT polarization in tumor samples from patients with ovarian cancer, and subsequently used transcriptome-driven, promoter-based bioinformatics analyses to identify gene regulatory pathways that potentially may underlie these changes.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Because chronic stress can dampen the immune response to the influenza vaccine in older populations, an ongoing RCT is examining the effects of a remotely delivered CBSM intervention on stress and immunologic responses to the influenza vaccine in distressed older women who are receiving primary treatment for breast cancer . With evidence that stress processes contribute to immunologic and tumor cell biology changes and poorer clinical outcomes in skin, lung, ovarian, renal, hepatocellular, and hematologic cancers, it is imperative that trials evaluate the effects of SM interventions on stress, immunologic outcomes, and health outcomes in these and other cancers.…”
Section: Sm and The Immune Processes In Patients With Cancermentioning
confidence: 99%
“…61 Secondary analyses implicated the upregulation of genes associated with heightened sympathetic nervous system (SNS) activity and NF-κB family transcription factors. 61 Thus, during the perisurgical period of ovarian cancer, as in the case of breast cancer 56 and RCC, 57 greater adversity is associated with greater inflammatory signaling and processes favoring metastasis and poorer clinical outcomes.…”
Section: Chronic Stress-induced Exacerbation Of Chronic Inflammationmentioning
confidence: 99%